Strategi Pemerintah Desa dalam Pemberdayaan Ekonomi Keluarga sebagai Upaya Penanggulan Kemiskinan di Desa Tanjung Rejo Kecamatan Percut Sei Tuan - Dewi Romantika Tinambunan; Putri Widia Ningsih; Talita Sembiring; Kania Nova Ramadhani; Halking Halking (Pusat Riset dan Inovasi Nasional, 2026)
Using qualitative and descriptive approaches, this study aims to explain how the village government of Tanjung Rejo, Percut Sei Tuan District, uses family economic empowerment strategies to combat poverty. The purpose of this approach is to describe the process, form, and impact of the economic empowerment strategies implemented by the village government. Data was collected through documentation, in-depth interviews, and observation. Village officials, community leaders, and villagers directly involved in the family economic empowerment program were the research informants. The results of the study show that the Tanjung Rejo Village government has used various strategies to boost the family economy. These strategies include providing entrepreneurship training, providing small business capital assistance, and forming joint business groups to improve the community's economy. Increased family income, business skill development, and improved economic independence of the village community are all positive outcomes of this approach. However, the program still faces several challenges, such as budget shortages, low community participation, and a poor monitoring and evaluation system. Overall, the Tanjung Rejo village government uses the family economic empowerment program to reduce poverty and improve family welfare.